SINTESA TEORI KONSTRUKSI SOSIAL REALITAS DAN KONSTRUKSI SOSIAL MEDIA MASSA - Hadiwijaya, Achmad Suhendra (DIALEKTIKA KOMUNIKA: Jurnal Kajian Komunikasi dan Pembangunan Daerah, 2023)
The theory of the social construction of reality and the theory of the social construction of mass media are still partially discussed. Several previous pieces of research have not yet correlated, elaborated, or synthesized from the theoretical aspect. Even though much has been said about the social construction of reality, media consumers are heavily influenced by media "made" constructions. The research aims to synthesize the Bergerian theory of social reality construction (Berger and Luckmann) with the Bunginan theory of social reality construction (Burhan Bungin). The method used is a literature study. The results showed that the synthesis of the social construction theory of reality and the social construction of mass media reality produced a thesis understanding of an objective and subjective reality which was sufficiently understood through the social construction theory of mass media reality. This is considering the individual phenomenon which, in all durations of daily life, cannot be separated from the role of social media interaction. They externalize, objectify as well as internalize reality based on mass media references. In the hierarchy, the social construction theory of reality can be placed as a grand theory by considering genealogical aspects, while the social construction theory of mass media reality can be placed as a middle-rank theory. This is of course related to the more universal focus on social construction of reality.